Development and performance evaluation of a precision seeder for sustainable rice cultivation - Prabhat Kumar Guru; Atul Kumar Shrivastava; Suryakanta Khandai; Rabe Yahaya; Sudhanshu Singh; Virender Kumar; Priyanka Tiwari; Manoj Kumar (Results in Engineering)
Water scarcity, labor constraints, and the need for sustainable farming practices have highlighted the limitations of traditional rice transplanting methods, driving interest in Direct Seeded Rice (DSR). To address these challenges, a precision hill seeder was developed and evaluated under puddled soil conditions to enhance efficiency, productivity, and nitrogen use efficiency in rice cultivation. The self-propelled machine features a 4 hp air-cooled diesel engine, adjustable seed and fertilizer boxes, an inclined seed plate metering unit, and a float-and-furrow system, enabling precise seeding with consistent hill-to-hill spacing and simultaneous deep fertilizer placement. Performance evaluation revealed key results: an operating speed of 1.7 km h-1, a seed rate of 21.5 kg ha-1, a fertilizer application rate of 86.5 kg ha-1, a field efficiency of 79.5 %, and a fuel consumption of 0.8 l h-1. The seeder achieved a 25 % reduction in operational costs per hectare and an average 7.7 % increase in crop yield compared to manual drum seeding. These findings demonstrate the potential of the precision hill paddy seeder to transform rice cultivation by addressing labor and resource constraints while improving yield and operational efficiency.